Molecular characterization and genetic diversity of Jatropha curcas L. in Costa Rica - Vásquez-Mayorga, Marcela (2017)
We estimated the genetic diversity of 50 Jatropha curcas samples from the Costa Rican germplasm bank using 18 EST-SSR, one G-SSR and nrDNA-ITS markers. We also evaluated the phylogenetic relationships among samples using nuclear ribosomal ITS markers. Non-toxicity was evaluated using G-SSRs and SCARs markers. A Neighbor- Joining (NJ) tree and a Maximum Likelihood (ML) tree were constructed using SSR markers and ITS sequences, respectively. Heterozygosity was moderate (He D 0.346), but considerable compared to worldwide values for J. curcas. The PIC (PIC D 0.274) and inbreeding coefficient (f D0:102) were both low. Clustering was not related to the geographical origin of accessions. International accessions clustered independently of collection sites, suggesting a lack of genetic structure, probably due to the wide distribution of this crop and ample gene flow. Molecular markers identified only one non-toxic accession (JCCR-24) from Mexico. This work is part of a countrywide effort to characterize the genetic diversity of the Jatropha curcas germplasm bank in Costa Rica.